2000
DOI: 10.1034/j.1399-0004.2000.570107.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of education and counselling offered by a familial colorectal cancer clinic

Abstract: We have evaluated whether or not client expectations, in terms of education and information needs, have been met by a multi-disciplinary familial colorectal cancer clinic. The study used a pre- and post-clinic questionnaire design and 126 (84 women, 42 men) clients of the clinic participated. The most common reason for coming to the clinic is to 'find out whether there is a gene for colorectal cancer in the family', followed by 'to reduce risk for bowel cancer' and 'concern for children's risk'. Clients would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 25 publications
7
48
1
Order By: Relevance
“…Important informational motives were to discuss own and/or family members' risk of cancer and to receive information on early detection of cancer and preventive actions (Bleiker et al, 1997;Brain et al, 2000;Collins et al, 2000a;Hallowell et al, 1997;Julian-Reynier et al, 1996;van Asperen et al, 2002), know the risk for one's children, or of passing on increased susceptibility to them (Bleiker et al, 1997;Collins et al, 2000a;Julian-Reynier et al, 1996;van Asperen et al, 2002), and to discuss one's family history and/or find out about genetic testing (Brain et al, 2000;van Asperen et al, 2002). A recent review (Bleiker et al, 2003) showed that these were also main motives for requesting genetic testing for hereditary cancer.…”
Section: Presumed Type Of Needs and Preferences Prior To Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…Important informational motives were to discuss own and/or family members' risk of cancer and to receive information on early detection of cancer and preventive actions (Bleiker et al, 1997;Brain et al, 2000;Collins et al, 2000a;Hallowell et al, 1997;Julian-Reynier et al, 1996;van Asperen et al, 2002), know the risk for one's children, or of passing on increased susceptibility to them (Bleiker et al, 1997;Collins et al, 2000a;Julian-Reynier et al, 1996;van Asperen et al, 2002), and to discuss one's family history and/or find out about genetic testing (Brain et al, 2000;van Asperen et al, 2002). A recent review (Bleiker et al, 2003) showed that these were also main motives for requesting genetic testing for hereditary cancer.…”
Section: Presumed Type Of Needs and Preferences Prior To Counselingmentioning
confidence: 99%
“…It is therefore likely that counselees wish to discuss family issues during counseling. Finally, results suggest that counselees often are unfamiliar with the process of genetic counseling, including uncertainty about what will occur during counseling (Collins et al, 2000a;Hallowell et al, 1997) and the exact role of the counselor amongst other health care providers (Bernhardt et al, 2000). Apart from discussing medical and emotional issues, counselees may thus also wish to receive information on the procedure of counseling.…”
Section: Presumed Type Of Needs and Preferences Prior To Counselingmentioning
confidence: 99%
“…A total of 59.6% of respondents indicated they had received less than enough information about this risk. Similarly, the mean satisfaction rating for the amount of support they had received about prostate cancer in the family was 2.40 (SD ϭ 0.92, range "not enough" [1], "some but not enough" [3], "enough" [5]), with 43.9% responding they had received no support and a further 43.6% responding they had not received enough support. Kruskal-Wallis tests showed no significant differences between the men's ratings for the amount of information they had received ( 2 ϭ 0.2.18, P ϭ .89) depending on whether men were unpartnered or had a partner with low or high concern about family history.…”
Section: Genetic Services For Menmentioning
confidence: 99%
“…When asked to comment on their concern regarding prostate cancer in the family, the mean concern rating was 3.48 (standard deviation [SD] ϭ 1.16, range "not at all" [1] to "ex- …”
Section: Need For Prostate Cancer Information and Supportmentioning
confidence: 99%
See 1 more Smart Citation